Do asymmetry scores influence speed and power performance in elite female soccer players? - Loturco, Irineu; Pereira, Lucas A.; Kobal, Ronaldo; Abad, Cesar C. C.; Rosseti, Marcelo; Carpes, Felipe P.; Bishop, Chris (Biology of Sport, 2019)
This study examined the relationships between vertical jump asymmetries and speed and power performance in elite female soccer athletes. Sixteen professional female soccer players (age: 23.0 ± 3.8 years; body mass: 60.2 ± 7.3 kg; height: 165.1 ± 5.5 cm) from the same professional club participated in this study. Athletes performed unilateral and bilateral squat jumps (SJ) and countermovement jumps (CMJ) on a portable force plate; 30-m sprinting test; Zigzag change-of-direction (COD) test; and muscle power testing using the jump squat (JS) exercise. Asymmetry scores were obtained from the results of the unilateral SJ and CMJ by the percentage difference between the dominant and non-dominant legs. The Pearson product-moment coefficient of correlation was used to analyse the correlations between the bilateral and unilateral vertical jump variables and the physical tests. The bilateral vertical jump performance (in both SJ and CMJ) was closely related to sprinting and JS power performances (r values ranging from 0.50 to 0.73; P< 0.05). In contrast, no significant associations were found between jump asymmetries and performance measures. Our data suggest that asymmetry scores derived from unilateral vertical jumps are not capable of influencing the speed-power performance of professional female soccer players.